Durable antibacterial finishing of cotton fabric based on thiol–epoxy click chemistry. Issue 31 (28th March 2017) - Yu, Dan; Xu, Lijin; Hu, Yi; Li, Yani; Wang, Wei
Abstract : This research proposes a method based on thiol–epoxy click chemistry to achieve durable antibacterial properties on cotton fabrics. Abstract : This research proposes a method based on thiol–epoxy click chemistry to achieve durable antibacterial properties on cotton fabrics. The cotton fabric was first modified with 3-mercaptopropyltriethoxysilane (KH-580) to introduce thiol groups. Then, cotton fabric was treated with a quaternary ammonium salt by thiol–epoxy click chemistry. The surface morphology of the treated fabrics and the reaction mechanism were confirmed by FTIR, EDS, and SEM. The antibacterial activity, dyeing performance, and mechanical properties of the treated cotton fabrics were also assessed. The E. coli antibacterial rate was about 99.44% and the S. aureus antibacterial rate was about 95.93%, with only a slight decrease after 30 cycles of washing, to 93.89% and 88.62%, respectively. The results demonstrated that this treatment effectively imparted the cotton fabric with durable antibacterial properties due to the chemical bonding formed between the quaternary ammonium salt and the substrate.